Efficient TiO2-SiO2 hybrid nanocoolant - Azmi, W. H.; R., Mamat; Khamisah, Abdul Hamid (2018)
Modern and compact design → heat generation / dissipation → Conventional coolant → heat transfer rate → Limitation with existing single nanofluids: less in stability, more pumping power, high production cost.